Influence of oxide buffer layers on the growth of carbon nanotube arrays on carbon substrates. (June 2015) - Quinton, Betty T.; Leedy, Kevin D.; Lawson, Jacob W.; Tsao, Bang; Scofield, James D.; Merrett, Joseph N.; Zhang, Qiuhong; Yost, Kevin; Mukhopadhyay, Sharmila M.
Abstract: Controllable growth of carbon nanotube (CNT) arrays on carbon substrates requires an oxide buffer layer material such as Al2 O3 and SiO2 . This research analyzes the influence of these buffer layers on a model carbon substrate composed of pyrolyzed carbon film on flat silicon. Electron microscopy was used to analyze nanocatalyst morphology, particle density, CNT nucleation rate, and CNT morphology for selected growth conditions. It was observed that nanotubes grown on Al2 O3 buffer layers had the fastest CNT nucleation rates and more uniform tube diameters, with residual nanocatalyst particles having elongated shapes. In contrast, CNTs formed on SiO2 buffer layers nucleated slower and had more variation in tube diameters, while the nanocatalyst particles remained spherical. Comparisons among SiO2 buffer layers deposited using three different techniques—atomic layer deposition, microwave plasma enhanced chemical vapor deposition and thermal oxidation—indicated that surface roughness plays an important role. Silica layers with the highest roughness had the highest catalytic particle density and tallest carpet height for identical growth conditions. These results provide new insight into the importance of buffer layer chemistry and morphology on growth and controllability of CNT arrays.